2008
DOI: 10.1038/ncb1718
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for phagosome maturation during engulfment of apoptotic cells

Abstract: The efficient removal of apoptotic cells is critical for the physiological well-being of the organism 1 Ã 4 ; defects in corpse removal have been linked to autoimmune disease 4,5 . While several players regulating the early steps of corpse recognition and internalization have been characterized 6 , the molecules and mechanisms relevant to the subsequent processing of the internalized corpses are poorly understood. Here, we identify a novel pathway for the processing of internalized apoptotic cells in C. elegan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
367
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(389 citation statements)
references
References 58 publications
19
367
1
2
Order By: Relevance
“…19,20 Once internalized, phagolysosome maturation occurs through the action of several Rab-family GTPases eventually leading to the degradation of the ingested cell corpse. 21 'Find-me' signals Both non-professional phagocytes and resident professional phagocytes can clear dying cells under homeostatic conditions. Although neighboring cells may not need to 'migrate' toward an apoptotic cell to engulf, motile phagocytes such as a resident macrophage likely do.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…19,20 Once internalized, phagolysosome maturation occurs through the action of several Rab-family GTPases eventually leading to the degradation of the ingested cell corpse. 21 'Find-me' signals Both non-professional phagocytes and resident professional phagocytes can clear dying cells under homeostatic conditions. Although neighboring cells may not need to 'migrate' toward an apoptotic cell to engulf, motile phagocytes such as a resident macrophage likely do.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…PI(3)P signaling is involved in the formation and maturation of both autophagosomes and phagosomes (13,14). Vps34 also regulates apoptotic cell engulfment (15). Although it has been reported that Beclin 1 is involved in the clearance of apoptotic cells during embryonic development by regulating the expression of PS (16), whether or not Beclin 1 plays a role in apoptotic cell engulfment by phagocytes is unclear.…”
mentioning
confidence: 98%
“…It has been reported that PI(3)P is generated by the VPS34-PI3K complex on the phagosome membrane during apoptotic cell engulfment (15). The FYVE zinc-finger domain binds to PI(3)P. Therefore, a fluorescent protein-fused FYVE domain is widely used as a marker for PI(3)P. Accordingly, we examined the co-localization of an mCherry-fused FYVE domain (mCherry-FYVE) with Beclin 1. mCherry-FYVE accumulation was observed around the phagocytic cups, and there was prominent co-localization with Beclin 1 (Fig.…”
Section: Recruitment Of Beclin 1 To Early Phagocytic Cup With Pi3kmentioning
confidence: 99%
“…2b). DYN-1 is also essential for the degradation of apoptotic cells through its fundamental role in phagosome maturation: DYN-1 is necessary for recruitment and fusion of endosomes and lysosomes to phagosomes [121,123,124] (Fig. 2b).…”
Section: Ndpks As Signal Integrators Of Nutrient Supplymentioning
confidence: 99%
“…2b). Recruitment of two endosomal markers, RAB-5 and RAB-7, also relies on DYN-1 activity [122][123][124]. RAB-5 is important for promoting the maturation of phagosomes containing apoptotic cells [124,125].…”
Section: Ndpks As Signal Integrators Of Nutrient Supplymentioning
confidence: 99%